Is Holiday Overview in Indonesia General Election Legal? - Wilma Laura Sahetapy, Tomy Michael, Hufron, (Opción, 2019)
The aim of the study is to investigate whether holiday overview in Indonesia general election is legal or not by using a normative legal method. As a result, restrictions on rights even though national holidays can also make a person not to take part in elections will weaken the nature of the election itself. In conclusion, elections contain choices and do not vote, both of which are citizens’ rights without government interventions.